PENGGUNAAN IQRO’ BRAILLE UNTUK MEMPERLANCAR KEMAMPUAN MEMBACA AL-QUR’AN SISWA TUNANETRA KELAS III DI SDLB - KURNIA, KUKUH (Jurnal Pendidikan Khusus, 2016)
ABSTRACT Visual impairment caused learning disabilities, it was read, and also read Koran. Learning process must be given by a suitable method and media which appropriate with their characteristics. The purpose of this research was to describe the efctiveness of using iqro’ braille  media improving ability of reading Al-Qur’an to the third class of students with visual impairment  in  SDLB-A  YPAB Surabaya. This research was use quantitative approach, pre eksperimental researche with one group pre test-post test design.  A number of students 3rd grades was involved in this research. Data was collected by test method and use sign test nonparametric statistic analysis. Based on pre test-post test  data analysis it obtained positive change. Mean score on pre test was 44.17, and rised 81.67, after given intervention  during 4 meeting. The data research result was known n=6, with X= 5.5, = 5% (0,05),  and µ = 3.0 tested by sign test. Then,  Z count was (Zh) = 2.03 and compared with two side sign test 1.64, so Zh > Z tabel, it was 2.03 > 1.64 which interpreted that, there was an effect of using iqro’ braille  media improving ability of reading Al-Qur’an to the third class of students with visual impairment  in  SDLB-A  YPAB Surabaya.    Kata kunci : reading Al-Qur’an, iqra Braille media.